The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.4238/gmr16039794
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Genetic diversity among 16 genotypes of Coffea arabica in the Brazilian cerrado.

Abstract: ABSTRACT. For the selection of coffee plants that have favorable characteristics, it is necessary to evaluate variables related to production. Knowledge of the genetic divergence of arabica coffee is of extreme importance, as this knowledge can be associated with plant breeding programs in order to combine genetic divergence with good productive performance. The objective of this study was to evaluate the genetic divergence among 16 genotypes of Coffea arabica with the purpose of identifying the most dissimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…In the present work, 16 C. arabica cultivars were selected for analysis, according to their global commodity value in different countries. C. arabica lineages analyzed in this study were classified into two groups that agree with previously reported phylogenies obtained through other methods (Anthony et al, 2002;Machado et al, 2017;Steiger et al, 2002). The first group corresponds to the 'Bourbon' and 'Typica' genetic family; the most important cultivars of this group are 'Pluma Hidalgo' and 'Maragogype', which are natural mutations of 'Typica'.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the present work, 16 C. arabica cultivars were selected for analysis, according to their global commodity value in different countries. C. arabica lineages analyzed in this study were classified into two groups that agree with previously reported phylogenies obtained through other methods (Anthony et al, 2002;Machado et al, 2017;Steiger et al, 2002). The first group corresponds to the 'Bourbon' and 'Typica' genetic family; the most important cultivars of this group are 'Pluma Hidalgo' and 'Maragogype', which are natural mutations of 'Typica'.…”
Section: Discussionsupporting
confidence: 85%
“…In conclusion, FCM was used for the estimation of genome size and GC% content in 16 C. arabica cultivars, which allowed the identification of different groups that agree with the previously grouping described, obtained through phylogenetic and amplified fragment length polymorphism analysis (Anthony et al, 2002;Giles et al, 2019;Machado et al, 2017;Steiger et al, 2002). This information could be helpful for C. arabica breeding programs, given the paucity of genome size studies with FCM in different important C. arabica cultivars (such as the group corresponding to the 'Bourbon' and 'Typica' genetic family hybrids and artificial crosses).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These nine clusters are considered divergent among each other regarding the foliar nutrient contents from the C. canephora genotypes cultivated at an altitude of 850 meters, where high diversity was identified in terms of foliar nutrient contents. The study of genetic diversity using multivariate techniques is important for planning and defining work strategies in breeding programs (Guedes et al, 2013;Machado et al, 2017). In fact, the use of plant material with genetic variability is determinant for successive breeding programs, providing greater gains in selection (Cruz et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The berries' anatomical variations, such as the diameter of the crown, may influence the penetration behavior of H. hampei (MACHADO et al, 2017). Chemical characteristics are also important determinants of insect behavior (BRUCE; PICKETT, 2011), especially that of the females, which can sense the different volatile compounds released by attacked and intact fruit and differentiate among them (JARAMILLO et al, 2013;BRASSIOLI-MORAES et al, 2019).…”
Section: Introductionmentioning
confidence: 99%